Contingency management for individuals with chronic health conditions: A systematic review and meta-analysis of randomized controlled trials. (January 2021) - Ellis, Jennifer D.; Struble, Cara A.; Fodor, Marina C.; Cairncross, Molly; Lundahl, Leslie H.; Ledgerwood, David M.
Abstract: Background: Contingency management (CM) interventions involve providing reinforcement for engaging in a desired behavior, and have been shown to increase treatment adherence and promote abstinence in the treatment of substance use disorders. This review was conducted to systematically review the literature on the effectiveness of CM when applied to a range of medical conditions outside of substance use disorders. Method: The authors identified a total of 24 randomized studies examining the effects of CM on four outcomes: weight change, physical activity, medication/device adherence, and viral load that were included in the qualitative summary, and 20 studies included in the meta-analysis. Results: CM was associated with positive outcomes for physical activity and medication/device adherence compared to control conditions. Findings with weight loss and viral load were more mixed, and evidence for publication bias was found for both outcomes. The effects of CM tend to dissipate when the contingency is removed. Heterogeneity was observed across most outcomes. Limitations and Conclusions: This review provides preliminary support for the use of CM in increasing physical activity and improving adherence to medication for chronic health conditions while reinforcement is ongoing. Future studies should examine potential moderators and identify strategies to maintain these changes over time. Highlights: CM performed better than control across studies in improving adherence and exercise. Outcomes for weight and viral load showed promise, but effects were small. Effects of CM were not maintained at follow-up. Significant heterogeneity across studies was observed.